MANAGERIAL COMPETENCE OF PRESCHOOL EDUCATION LEADERS IN INTERNATIONAL PRACTICE - Berdimuratov Adkham Khayrulla ugli; Shamsiyeva Nigina Baxriddin qizi (Modern American Journals, 2025)
This article analyzes the managerial competence of preschool education leaders and the factors influencing its development based on the experience of foreign countries. Additionally, proposals are developed for enhancing the management capacity of preschool education leaders in Uzbekistan, drawing on international best practices.
Keywords: Managerial competence, preschool education, education leader, management competencies, international experience, leadership training, education policy, pedagogical management.